2001
DOI: 10.1016/s0168-3659(00)00359-x
|View full text |Cite
|
Sign up to set email alerts
|

Ion-exchange fibers and drugs: an equilibrium study

Abstract: The purpose of this study was to investigate the mechanisms of drug binding into and drug release from cation-exchange fibers in vitro under equilibrium conditions. Ion-exchange groups of the fibers were weakly drug binding carboxylic acid groups (-COOH), strongly drug binding sulphonic acid groups (-SO H), or combinations thereof. Parameters determining 3 the drug absorption and drug release properties of the fibers were: (i) the lipophilicity of the drug (tacrine and propranolol are lipophilic compounds, nad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 15 publications
6
74
0
Order By: Relevance
“…25) Electrostatic interaction governs the equilibrium distribution of the drug species between the resin and solution phases. [26][27][28] The drug resinate is stable in salivary pH during its disintegration in the oral cavity. Taste masking evaluation by volunteers also indicated that the resinate formation was an efficient method of taste masking for this drug (Table 3).…”
Section: Molecular Properties Of Drug-resin Complexes Xray Diffractomentioning
confidence: 99%
“…25) Electrostatic interaction governs the equilibrium distribution of the drug species between the resin and solution phases. [26][27][28] The drug resinate is stable in salivary pH during its disintegration in the oral cavity. Taste masking evaluation by volunteers also indicated that the resinate formation was an efficient method of taste masking for this drug (Table 3).…”
Section: Molecular Properties Of Drug-resin Complexes Xray Diffractomentioning
confidence: 99%
“…[27][28][29] Increasing the electrolyte concentration decreases the Donnan potential and, hence, the electrostatic affinity between the drug and the ion exchanger, thus tending to increase drug release. The influence of salt concentration on the release rate can be explained by solute diffusion.…”
Section: Drug Release From Drug-indion Complexmentioning
confidence: 99%
“…It has been reported that PRM depolarize taste cells by closing K + channels and produce bitterness (2). Palatable formulation development is one of the most difficult tasks, although various taste masking techniques such as the addition of sweeteners and flavors (3), coating with polymers (4), adsorption to ion-exchange resin (5,6), and chemical modifications such as the use of insoluble prodrugs (7,8) have been reported. Each technique has its own disadvantages.…”
Section: Introductionmentioning
confidence: 99%